Changes in Gene Expression in Regions of the Extended Amygdala of Alcohol-Preferring Rats Following Binge-Like Alcohol Drinking - McBride, William J. (2010)
The objective of this study was to determine time-course changes in gene expression within two regions of the extended amygdala following binge-like alcohol drinking by alcohol-preferring (P) rats. Adult male P rats were given 1-hr access to 15 and 30% ethanol three times daily for 8 weeks. Rats (n = 10/time point for ethanol and n = 6/time point for water) were killed by decapitation 1, 6 and 24 hr after the last drinking episode. RNA was prepared from individual micropunch samples of the nucleus accumbens shell (ACB-shell) and central nucleus of the amygdala (CeA); analyses were conducted with Affymetrix Rat 230.2 chips. Ethanol intakes were 1.5–2 g/kg for each of the 3 sessions. There were no genes that were statistically different between the ethanol and water groups at any individual time point. Therefore, an overall effect, comparing the water and ethanol groups, was determined. In the ACB-shell and CeA, there were 276 and 402 probe sets for named genes, respectively, that differed between the two groups. There were 1.5- to 3.6- fold more genes with increased than decreased expression in the ethanol drinking group, with most differences between 1.1- to 1.2-fold. Among the differences between the ethanol and water groups were several significant Biological Processes categories that were in common between the 2 regions (e.g., synaptic transmission, neurite development); however, within these categories, there were few genes in common between the two regions. Overall, the results indicate that binge-like alcohol drinking by P rats produces region-dependent changes in the expression of genes that could alter transcription, synaptic function and neuronal plasticity in the ACB-shell and CeA; within each region, different mechanisms may underlie these alterations, since there were few common ethanol-responsive genes between the ACB-shell and CeA.